ceNEAT: Neuroevolução de topologias aumentantes com melhorias culturais - Paulino, Arthur Leonardo de Alencar (2019)
Knowledge transmitted between generations by non-genetic means can be understood as culture. The capacity of individuals from a certain species to teach and learn plays a fundamental role in directing the evolutionary process. The goal of this work is to list and evaluate ways of enhancing the Neuroevolution of Augmenting Topologies with learning processes. The parameters involved in the analysis contemplate the methods Backpropagation and Extreme Learning Machine, the individuals to be taught, the moment from which culture manifests in the system and the nature of the lessons to be learned. The results show that cultural enhancement, as well as some of the variations on the proposed parameters, accelerates the evolutionary process’ convergence.